[Sheep Along Hvalfjord] - Streng, Evelyn Fiedler (1975)
Photograph of sheep at Hvalfjord in Iceland. Two white sheep with horns sit behind brown rocks covered in green grass. A brown road is visible along the left edge of the photograph leading to two metal poles on the right. A brown, flat mountain is visible in the background behind a deep blue fjord between it.